A cross-sectional observational study of clinical spectrum and prevalence of fixed food eruption in a tertiary care hospital - Loknandini Sharma; Reetu Agarwal; Ajay Chopra; Barnali Mitra (Wolters Kluwer Medknow Publications, 2020)
Background: Fixed food eruption (FFE) is a rare type of hypersensitivity reaction occurring after ingestion of some food items in the form of recurrent erythematous patches, bullae, vesicle, or pustule at the same site after ingestion of same or related food products. Various items listed responsible for causing FFE include tree nuts, groundnuts, legumes, lentils, eggs, fruits like kiwi, strawberry, tonic water, and tartrazine. Its more commonly reported in developed countries with no Indian studies as of yet. We studied the clinical spectrum and prevalence of FFE in a tertiary care hospital. Objective: To study the prevalence and pattern of FFE after eliminating all other possible causes including drug rash. Materials and Methods: A cross-section observational study of 27 consecutive patients suspected to have fixed food eruption after eliminating all possibilities of any drug reaction to the best of our knowledge. Informed consent was obtained from the patients, and ethical clearance was taken from the hospital ethical committee. Results: A total of 27 patients were studied out of which 18 (66.66%) were females and 9 (33.33%) were males. The prevalence of fixed food eruption was calculated to be 0.072%.Fixed food eruption was noted secondary to cashew nuts (14.8%), almonds (7.4%), walnut (7.4%), pistachio (3.7%), strawberry (3.7%), kiwi (3.7%), and cheese crisps (3.7%). Conclusion: This observational study highlights the varied patterns of fixed food eruptions as well as the burden of disease in population secondary to certain diets.